Supporting Academic Writing and Publication Practice: PhD Students in Engineering and their Supervisors - Kasparkova, Alena; Etchegoyen Rosolová, Kamila (Journal of Academic Writing, 2020)
Supporting Academic Writing and Publication Practice: PhD Students in Engineering and their Supervisors This poster documents the bottom-up efforts leading to the establishment of an academic writing support program for doctoral students at an engineering university in the Czech Republic (CR). To defend their dissertation, by law Czech doctoral students have to have published their research. Moreover, many faculties require their doctoral students to publish in prestigious English-medium journals, which is a challenge even for the students’ supervisors. Although publication requirements prior to dissertation defence are becoming common in many countries (Kamler and Thompson, 2014; Kelly, 2017), Czech students often face a challenge of writing in the absence of any prior writing support, where insufficient knowledge of English only adds an extra hurdle to the already difficult task of argumentation absent in Czech schooling. CR has a comparatively high number of doctoral students, but also alarmingly high drop-out rates with more than 50% students not finishing their studies (Beneš et al., 2017). In part, this is due to the students’ difficulties to publish (National Training Fund, 2019). This challenge could be addressed with systematic writing development, but Czech educators and dissertation supervisors are not commonly aware of composition being teachable as we learned from our preliminary study on writing support in doctoral programs in several Czech universities (Rosolová & Kasparkova, in press). While supervisors and university leaders tended to see writing development as a responsibility of the students, the doctoral students were calling for systematic support. We strive to bring attention to the complexity of writing development and introduce a discourse on academic writing that conceives of academic writing as a bundle of analytical and critical thinking skills coupled with knowledge of rhetorical structures and different academic genres. We show how these skills can be taught through a course drawing on the results from a needs analysis survey among engineering doctoral students, the target population for this course (for more information on the survey, see Kasparkova & Rosolová, 2020). In the survey, students expressed a strong interest in a blended-learning format of the course, which we base on a model of a unique academic writing course developed for researchers at the Czech Academy of Sciences, but not common in Czech universities. Our course is work in progress and combines writing development with library modules that frame the whole writing process as a publication journey ranging from library searches, to a selection of a target journal and communication with reviewers. Because we are well aware that a course alone will not trigger a discourse on writing development in Czech higher education, we also plan on involving a broader academic community through workshops for supervisors and a handbook on teaching academic writing and publishing skills for future course instructors. Colleagues at EATAW 2019 conference commented on the poster sharing their difficulties from the engineering context and for instance suggested a computer game to engage engineers. This resonated with our plan to invite our engineers into the course through a geo-caching game – for more, see Kasparkova & Rosolová (2020). References Beneš, J., Kohoutek, J., & Šmídová, M. (2017). Doktorské studium v ČR [Doctoral studies in the CR]. Centre for Higher Education Studies. https://www.csvs.cz/wp-content/uploads/2018/10/Doktorandi_final_2018.pdf Rosolová, K. E., & Kasparkova, A. (in press). How do I cook an Impact Factor article if you do not show me what the ingredients are? Educare. https://ojs.mau.se/index.php/educare Kamler, B., & Thomson, P. (2014). Helping Doctoral Students Write (2nd edition). Routledge. Kasparkova, A., & Rosolová, K. (2020). A geo-caching game ‘Meet your Editor’ as a teaser for writing courses. 2020 IEEE International Professional Communication Conference (ProComm), Kennesaw, GA, USA, 2020, pp. 87-91. https://doi.org/10.1109/ProComm48883.2020.00019 Kelly, F. J. (2017). The idea of the PhD: The doctorate in the twenty-first-century imagination. Routledge. National Training Fund. (2019). Complex study of doctoral studies at Charles University and recommendations to improve the conditions and results. Report for the Charles University Management. Prague.